EVALUASI PROGRAM SEKOLAH BERBASIS MODEL CIPP DALAM MENGUATKAN KARAKTER PROFIL PELAJAR PANCASILA DI SEKOLAH DASAR - Sugiyanto; Rahayu, Anny; Muhibbin, Ahmad; Susilo, Agus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to evaluate the strengthening program of the Profil Pelajar Pancasila (Pancasila Learner Profile) in elementary schools using the CIPP (Context, Input, Process, Product) evaluation model. The research employs a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The evaluation results indicate that the context and input components are in the "excellent" category. However, the process aspect requires optimization regarding the management of project implementation timing. Overall, the product evaluation demonstrates a significant improvement in students' independent and collaborative (gotong royong) characters. The program is effective in internalizing Pancasila values. The success of this program is highly influenced by the synergy between school leadership and teacher creativity in managing co-curricular projects. Field findings indicate that active parental involvement further accelerates the internalization of noble values outside the school environment. Despite administrative constraints, the integration of Pancasila values has fostered a more harmonious and tolerant educational climate. Research recommendations are directed toward the development of a digital assessment system to facilitate the continuous monitoring of student character development.